STUDENTS’ PERCEPTION AND THEIR ATTITUDE TOWARDS ENGLISH TEACHERS’ PERSONALITY - Masruddin Masruddin Masruddin; Henis Henis Pratiwi (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
This research aimed at finding out the types of English teacherpersonality based on students’ perception and how is their attitudetoward their English teacher personality. This research used descriptivequalitative method. The subject of the research were students of secondgrades at SMKN 1 Palopo and there were 4 teachers of English atSMKN 1 as focus of this research. The researcher used snowballsampling technique in taking 12 students as the respondents of thisresearch. The instrument of this research was interview. The result ofthis research shows that (a) in the eyes of the students, there were 3 English teachers who have good personality, they were warm, caring to students, sociable, knowledgeable, creative, cheerful, close to students, and explicit. Then, 1 teacher has bad personality, such as low motivation, boring, lazy and apathetic. (b) the students’ attitude toward their English teacher is determined by teacher personality. If the teacher has good personality, students’ attitude is positive. On the contrary, if the teacher has bad personality, students’ attitude is negative. In the view of students, a good teacher should be kind, humorist, good motivator, knowledgeable, creative, explicit, close to students and sociable. Then, most of the students perceive that the teacher personality influence their mood in learning English.Keywords: perception, attitude, teacher personality